Pakistan agri-food system: Assessment report - Davies, Stephen; Ejaz, Amna (International Food Policy Research Institute, 2025)
Despite agriculture’s central role in Pakistan’s economic growth, the sector continues to struggle with decades old structural issues and its performance is weak. Spending on subsidies for water, fertilizer, electricity, and wheat procurement reached US$1.25 billion in Punjab alone, far more than the funding provided for research and development. Inefficient and fragmented value chains, high post-harvest losses and transport costs, limited access to formal markets, dependence on subsidies, and underdeveloped storage and processing infrastructure are among the significant problems affecting agriculture. The deep-rooted traditional system, characterized by reliance on commission agents and the weak implementation of market reforms both restrict farmers’ bargaining power, especially for smallholder farmers. Moreover, although on average the country’s population is food secure in terms of caloric sufficiency, limited dietary diversity and inadequate access to nutritious foods cause widespread malnutrition.